FORCED STRING OSCILLATIONS UNDER THE INFLUENCE OF CONTINUOUS FORCE AND FORCES OF IMPULSE NATURE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The string oscillations of finite length with fixed ends, under the influence of a continuous force and forces of impulsive nature arising at some fixed moments of time are investigated.The mathematical model of such an oscillatory process is a string oscillation equation with homogeneous boundary conditions, inhomogeneous initial conditions and the condition of impulse action at fixed points of time.This work gives the solution of this problem in the form of a series on eigenfunctions of the Sturm-Louiville problem, the conditions under which the obtained series converges uniformly are specified.